A high performance water-based ink and preparation method thereof
By adding EDTA modified zirconium phosphate and titanate coupling agent 131 to the aqueous ink, the problems of poor thermal stability and insufficient mechanical properties of existing aqueous polyurethane inks were solved, and significant performance improvement was achieved, meeting the actual production needs.
Patent Information
- Application Number
- CN202411245819.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-09-06
AI Technical Summary
The existing water-based polyurethane inks have poor thermal stability and insufficient mechanical properties, making it difficult to meet the actual production needs.
By adding EDTA modified zirconium phosphate and titanate coupling agent 131 to the aqueous ink, the layer spacing of zirconium phosphate and the compatibility of illite with polyurethane is improved, thereby improving the mechanical properties and thermal stability of the aqueous ink.
The mechanical properties and thermal stability of the aqueous ink are significantly improved, and the actual production needs are met. The performance of the aqueous ink is further improved through the addition of the above two components.
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of water-based inks, and more specifically, relates to a high-performance water-based ink and a preparation method thereof. Background Art
[0002] As a type of environmentally friendly printing material, water-based ink has been valued in the printing field. Water-based ink is usually composed of water-based binders, pigments and various additives. The water-based binder disperses the pigment evenly and forms a film on the substrate to obtain a printed product. The performance of the water-based binder affects the printing properties of the ink, such as rheology, water resistance and adhesion to the substrate. The resins used as water-based binders mainly include water-based acrylic resins, polyvinyl alcohol and water-based polyurethane (WPU). Among them, water-based polyurethane has the characteristics of strong structural designability, easy use, safety and environmental protection, and can be used in gravure, screen and other printing fields. With the defects of water-based polyurethane such as low adhesion to the surface of low-polarity substrates, preparing high-performance WPU and improving the printing adaptability of water-based ink is one of the current research focuses.
[0003] CN118271900A discloses a quick-drying water-based ink and a preparation method thereof, wherein the water-based ink comprises the following raw materials in parts by weight: 30-40 parts of water-based polyurethane resin, 10-20 parts of methyl methacrylate, 0-8 parts of water-based pigment, 2-4 parts of zinc oxide quantum dots, 2-4 parts of biomass nanofibers, 0.5-0.8 parts of sodium dodecylbenzene sulfonate, 1-1.5 parts of polydimethylsiloxane, 5-7 parts of ethanol, and 15-20 parts of water. The present invention mixes the water-based polyurethane resin with the biomass nanofibers and simultaneously adds zinc oxide quantum dots with catalytic properties, which can effectively increase the drying speed of the water-based ink while reducing the volatile toxic components, and can also improve the structural integrity of the water-based ink and improve the performance of the product.
[0004] CN118165572A discloses an environmentally friendly water-based printing ink and a preparation process thereof. A double-bond terminated modified polyurethane emulsion is prepared with polyether diol, modified monomer, isophorone diisocyanate, dihydroxymethyl propionic acid and hydroxyethyl acrylate as raw materials. The modified polyurethane emulsion, butyl acrylate, methyl methacrylate and propylene sulfonic acid are polymerized to form polyacrylate on the side chain of the polyurethane molecular chain to prepare a connecting material. The connecting material, pigment, filler, auxiliary agent, lubricant, dispersant and defoamer are uniformly mixed to prepare the ink. The modified monomer contains an organic silicon molecular chain, so that the prepared polyurethane molecular chain has an organic silicon structure, which cooperates with the long-chain fluorocarbon on the side chain to enhance the water resistance of the water-based ink. The crossed molecular chain segments contain sulfonic acid groups, which have strong polarity and can generate hydrogen bonds, covalent bonds or ionic bonds with the substrate to improve the adsorption and adhesion of the ink.
[0005] CN117089036A discloses a two-component solvent-free polyurethane adhesive for water-based ink and a preparation method thereof, wherein the polyurethane adhesive comprises component A and component B, wherein component A is a polyurethane prepolymer with an NCO terminal group formed by the reaction of a polyhydroxy compound and a polyisocyanate compound; component B is a polyhydroxy compound selected from at least one of polyester polyols and polyether polyols with a functional group of more than two and / or isocyanate compound chain extension. The present invention prepares a polyurethane adhesive having good bonding properties in both water-based ink and organic solvent-based ink through an overall design such as the selection and content matching of components A and B. The solvent-free polyurethane adhesive of the present invention can have good ink matching and good peel strength when used in water-based ink, and has the advantages of good operating performance and the like.
[0006] CN116102919A discloses a water-based ink and a printing process thereof, and relates to the field of printing. The water-based ink comprises 15-45 parts by weight of water-based polyurethane, 5-15 parts by weight of water-based chloroacetic acid emulsion, 10-50 parts by weight of fluorine-modified polyacrylate emulsion, 3-5 parts by weight of colorant, 1-2 parts by weight of silane coupling agent, and 25 parts by weight of ethanol solution. The water-based ink can be dried quickly at 55-65°C, which is beneficial to improving the printing speed of PVC film and effectively reducing the deformation of PVC film due to high temperature.
[0007] That is, it can be seen that the existing water-based polyurethane inks have poor thermal stability and insufficient mechanical properties, and cannot meet the needs of actual production. Summary of the invention
[0008] The technical problem to be solved by the present invention is to overcome the defects and shortcomings of the prior art and provide a high-performance water-based ink and a preparation method thereof. In parts by weight, the present invention comprises the following components: 85-95 parts of water-based polyurethane; 5-7 parts of EDTA-modified zirconium phosphate; 4-6 parts of illite modified by titanate coupling agent 131; 1.5-2.5 parts of dispersant; 2-4 parts of defoamer; 1-2 parts of film-forming aid; 110-130 parts of water. The present invention can increase the interlayer spacing of zirconium phosphate by EDTA-modified zirconium phosphate, and can increase the mechanical properties and thermal stability of water-based ink, while the illite can be modified by titanate coupling agent 131 to improve the compatibility of illite with polyurethane, thereby improving the mechanical properties and thermal stability of water-based ink.
[0009] The purpose of the present invention is to provide a high-performance water-based ink.
[0010] Another object of the present invention is to provide a method for preparing a high-performance water-based ink.
[0011] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0012] A high-performance water-based ink, comprising the following components in parts by weight:
[0013] 85-95 parts of waterborne polyurethane;
[0014] 5-7 parts of EDTA-modified zirconium phosphate;
[0015] 4-6 parts of illite modified by titanate coupling agent 131;
[0016] 1.5-2.5 parts of dispersant;
[0017] 2 to 4 parts of defoaming agent;
[0018] 1-2 parts of film-forming aid;
[0019] 110-130 parts of water.
[0020] In the present invention, a preferred technical solution is that the preparation method of EDTA-modified zirconium phosphate comprises the following steps:
[0021] The zirconium source and phosphoric acid are ultrasonically dispersed in deionized water, and then transferred to a hydrothermal reactor for hydrothermal reaction, filtered, washed, and dried to obtain zirconium phosphate. The zirconium phosphate and ethylenediaminetetraacetic acid are ultrasonically dispersed in deionized water, stirred and reacted at 40-60° C. for 4-8 hours, filtered, washed, and dried to obtain EDTA-modified zirconium phosphate.
[0022] Preferably, the zirconium source is zirconium oxychloride, and the molar ratio of the zirconium source to phosphoric acid is 1:7-9.
[0023] Preferably, the hydrothermal reaction conditions are: hydrothermal reaction at 120-160° C. for 14-20 h; the drying is performed at 80-100° C. for 12-18 h; and the stirring reaction is performed at 40-60° C. for 4-8 h.
[0024] Preferably, the mass ratio of the zirconium phosphate to ethylenediaminetetraacetic acid is 5:0.4-0.8.
[0025] In the present invention, the preferred technical solution is that the preparation method of the titanate coupling agent 131 modified illite comprises the following steps:
[0026] (1) ultrasonically dispersing illite and CTAB in deionized water, then stirring and reacting, cooling to room temperature, filtering, washing, and drying at 60 to 90° C. for 10 to 14 hours to obtain CTAB intercalated illite;
[0027] (2) The CTAB intercalated illite and isopropyl titanate triisostearate were ultrasonically dispersed in ethanol for 10 to 30 minutes, and then stirred for reaction, filtered, washed, and dried at 60 to 90° C. for 12 to 18 hours to obtain illite modified by titanate coupling agent 131.
[0028] Preferably, in step (1), the mass ratio of illite to CATB is 10:0.6-1.2; and the stirring reaction is carried out at 50-70° C. for 4-8 hours.
[0029] Preferably, in step (2), the mass ratio of the CTAB intercalated illite to isopropyl titanate triisostearate is 1:5-9; and the stirring reaction is carried out at 60-80° C. for 8-12 hours.
[0030] Preferably, the dispersant is octanol polyoxyethylene ether; the defoamer is AFE-3168 silicone defoamer; and the film-forming aid is propylene glycol methyl ether.
[0031] Based on the above-mentioned method for preparing a high-performance water-based ink, the preparation method comprises the following steps:
[0032] The aqueous polyurethane, EDTA-modified zirconium phosphate, illite modified by titanate coupling agent 131, dispersant, defoamer, film-forming aid and water are stirred at a speed of 3000-4000 rpm for 1-3 hours to obtain the product.
[0033] The present invention has the following beneficial effects:
[0034] The present invention modifies zirconium phosphate by EDTA, thereby increasing the interlayer spacing of zirconium phosphate and increasing the mechanical properties and thermal stability of the water-based ink. The illite is modified by the titanate coupling agent 131, thereby improving the compatibility of illite with polyurethane, thereby improving the mechanical properties and thermal stability of the water-based ink. By adding the above two components, the mechanical properties and thermal stability of the water-based ink of the present invention are further improved, thereby meeting the needs of actual production. DETAILED DESCRIPTION
[0035] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0036] Waterborne polyurethane: solid content 36%; the dispersant is octanol polyoxyethylene ether; the defoamer is AFE-3168 silicone defoamer; the film-forming aid is propylene glycol methyl ether.
[0037] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0038] Example 1
[0039] A high-performance water-based ink, comprising the following components in parts by weight:
[0040] 90 parts of waterborne polyurethane;
[0041] EDTA modified zirconium phosphate 6 parts;
[0042] 5 parts of illite modified by titanate coupling agent 131;
[0043] 2 parts of dispersant;
[0044] 3 parts of defoaming agent;
[0045] 1.5 parts of film-forming aid;
[0046] 120 parts of water.
[0047] The preparation method of the EDTA-modified zirconium phosphate comprises the following steps:
[0048] 1 mol of zirconium oxychloride and 8 mol of phosphoric acid were ultrasonically dispersed in 250 mL of deionized water, and then transferred to a hydrothermal reactor, hydrothermally reacted at 140°C for 18 hours, filtered, washed, and dried at 90°C for 16 hours to obtain zirconium phosphate. 5 g of zirconium phosphate and 0.6 g of ethylenediaminetetraacetic acid were ultrasonically dispersed in 100 mL of deionized water, stirred and reacted at 50°C for 6 hours, filtered, washed, and dried at 90°C for 16 hours to obtain EDTA-modified zirconium phosphate.
[0049] The preparation method of the titanate coupling agent 131 modified illite comprises the following steps:
[0050] (1) 10 g of illite and 1 g of CTAB were ultrasonically dispersed in 150 mL of deionized water, and then stirred at 60 °C for 6 h, cooled to room temperature, filtered, washed, and dried at 80 °C for 12 h to obtain CTAB intercalated illite;
[0051] (2) 10 g of CTAB intercalated illite and 70 g of isopropyl titanate triisostearate were ultrasonically dispersed in 150 mL of ethanol for 20 min, then reacted at 70 °C for 10 h, filtered, washed, and dried at 80 °C for 16 h to obtain illite modified with titanate coupling agent 131.
[0052] A method for preparing a high-performance water-based ink comprises the following steps:
[0053] The aqueous polyurethane, EDTA-modified zirconium phosphate, illite modified by titanate coupling agent 131, dispersant, defoamer, film-forming aid and water are stirred at 3500 rpm for 2 hours to obtain the product.
[0054] Example 2
[0055] A high-performance water-based ink, comprising the following components in parts by weight:
[0056] 95 parts of waterborne polyurethane;
[0057] 5 parts of EDTA-modified zirconium phosphate;
[0058] 6 parts of illite modified by titanate coupling agent 131;
[0059] 1.5 parts of dispersant;
[0060] 4 parts of defoamer;
[0061] 1 part of film-forming aid;
[0062] 130 parts of water.
[0063] The preparation method of the EDTA-modified zirconium phosphate comprises the following steps:
[0064] 1 mol of zirconium oxychloride and 9 mol of phosphoric acid were ultrasonically dispersed in 250 mL of deionized water, and then transferred to a hydrothermal reactor, hydrothermally reacted at 160°C for 14 h, filtered, washed, and dried at 100°C for 12 h to obtain zirconium phosphate. 5 g of zirconium phosphate and 0.8 g of ethylenediaminetetraacetic acid were ultrasonically dispersed in 100 mL of deionized water, stirred and reacted at 60°C for 4 h, filtered, washed, and dried at 100°C for 12 h to obtain EDTA-modified zirconium phosphate.
[0065] The preparation method of the titanate coupling agent 131 modified illite comprises the following steps:
[0066] (1) 10 g of illite and 1.2 g of CTAB were ultrasonically dispersed in 150 mL of deionized water, and then stirred at 70 ° C for 4 h, cooled to room temperature, filtered, washed, and dried at 90 ° C for 10 h to obtain CTAB intercalated illite;
[0067] (2) 10 g of CTAB intercalated illite and 90 g of isopropyl titanate triisostearate were ultrasonically dispersed in 150 mL of ethanol for 30 min, then reacted at 80 °C for 8 h, filtered, washed, and dried at 90 °C for 12 h to obtain illite modified with titanate coupling agent 131.
[0068] The preparation method of a high-performance water-based ink is the same as that in Example 1.
[0069] Example 3
[0070] A high-performance water-based ink, comprising the following components in parts by weight:
[0071] 85 parts of waterborne polyurethane;
[0072] EDTA modified zirconium phosphate 7 parts;
[0073] 4 parts of illite modified by titanate coupling agent 131;
[0074] 2.5 parts of dispersant;
[0075] 2 parts of defoaming agent;
[0076] 2 parts of film-forming aid;
[0077] 110 parts of water.
[0078] The preparation method of the EDTA-modified zirconium phosphate comprises the following steps:
[0079] 1 mol of zirconium oxychloride and 7 mol of phosphoric acid were ultrasonically dispersed in 250 mL of deionized water, and then transferred to a hydrothermal reactor, hydrothermally reacted at 120°C for 20 h, filtered, washed, and dried at 80°C for 18 h to obtain zirconium phosphate. 5 g of zirconium phosphate and 0.4 g of ethylenediaminetetraacetic acid were ultrasonically dispersed in 100 mL of deionized water, stirred and reacted at 40°C for 4 h, filtered, washed, and dried at 100°C for 12 h to obtain EDTA-modified zirconium phosphate.
[0080] The preparation method of the titanate coupling agent 131 modified illite comprises the following steps:
[0081] (1) 10 g of illite and 0.6 g of CTAB were ultrasonically dispersed in 150 mL of deionized water, and then stirred at 50 °C for 8 h, cooled to room temperature, filtered, washed, and dried at 60 °C for 14 h to obtain CTAB intercalated illite;
[0082] (2) 10 g of CTAB intercalated illite and 50 g of isopropyl titanate triisostearate were ultrasonically dispersed in 150 mL of ethanol for 10 min, then reacted at 60 °C for 12 h, filtered, washed, and dried at 60 °C for 18 h to obtain illite modified with titanate coupling agent 131.
[0083] The preparation method of a high-performance water-based ink is the same as that in Example 1.
[0084] Comparative Example 1
[0085] Comparative Example 1 is substantially the same as Example 1, except that ethylenediamine is used instead of EDTA.
[0086] Comparative Example 2
[0087] Comparative Example 2 is substantially the same as Example 1, except that an equal amount of zirconium phosphate is used to replace EDTA-modified zirconium phosphate. The preparation method of the zirconium phosphate comprises the following steps:
[0088] 1 mol of zirconium oxychloride and 8 mol of phosphoric acid were ultrasonically dispersed in 250 mL of deionized water, and then transferred to a hydrothermal reactor, hydrothermally reacted at 140° C. for 18 h, filtered, washed, and dried at 90° C. for 16 h to obtain zirconium phosphate.
[0089] Comparative Example 3
[0090] Comparative Example 3 is basically the same as Example 1, except that: the preparation method of the illite modified by the titanate coupling agent 131 comprises the following steps: 10 g of illite and 70 g of isopropyl titanate triisostearate are ultrasonically dispersed in 150 mL of ethanol, ultrasonically dispersed for 20 min, then reacted at 70 ° C for 10 h, filtered, washed, and dried at 80 ° C for 16 h to obtain illite modified by the titanate coupling agent 131.
[0091] Comparative Example 4
[0092] Comparative Example 4 is substantially the same as Example 1, except that the illite modified by the titanate coupling agent 131 is not contained, and the amount of the EDTA-modified zirconium phosphate is 11 parts.
[0093] The mechanical properties of Examples 1-3 and Comparative Examples 1-4 were tested. The specific test results are shown in Table 1:
[0094] The water-based inks of Examples 1-3 and Comparative Examples 1-4 were attached to PET plastic substrates respectively, and the wear resistance and adhesion of the ink layers were tested according to the national standard GB / T7706-2008 "Letterpress Decorative Printing".
[0095] Table 1:
[0096] Wear resistance (%) Adhesion (%) Example 1 99.3 99.7 Example 2 98.3 98.6 Example 3 98.9 99.3 Comparative Example 1 97.8 98.1 Comparative Example 2 95.7 95.8 Comparative Example 3 98.2 98.4 Comparative Example 4 92.8 93.2
[0097] It can be seen from Table 1 that the high-performance water-based ink prepared by the present invention has excellent wear resistance and adhesion, and excellent mechanical properties. In addition, the thermal stability is also significantly improved by adding EDTA-modified zirconium phosphate and titanate coupling agent 131 to modify illite. That is, the high-performance water-based ink prepared by the present invention has excellent performance.
[0098] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A water-based ink, characterized in that: By weight, it includes the following components: 85-95 parts of waterborne polyurethane; 5-7 parts of EDTA-modified zirconium phosphate; 4-6 parts of illite modified by titanate coupling agent 131; 1.5-2.5 parts of dispersant; 2 to 4 parts of defoaming agent; Film-forming aids 1-2 servings; 110-130 parts of water; The preparation method of the EDTA-modified zirconium phosphate comprises the following steps: The zirconium source and phosphoric acid are ultrasonically dispersed in deionized water, and then transferred to a hydrothermal reactor for hydrothermal reaction, filtered, washed, and dried to obtain zirconium phosphate; the zirconium phosphate and ethylenediaminetetraacetic acid are ultrasonically dispersed in deionized water, stirred and reacted at 40 to 60° C. for 4 to 8 hours, filtered, washed, and dried to obtain EDTA-modified zirconium phosphate; the molar ratio of the zirconium source to the phosphoric acid is 1:7 to 9; the mass ratio of the zirconium phosphate to the ethylenediaminetetraacetic acid is 5:0.4 to 0.8; The preparation method of the titanate coupling agent 131 modified illite comprises the following steps: (1) ultrasonically dispersing illite and CTAB in deionized water, then stirring and reacting, cooling to room temperature, filtering, washing, and drying at 60 to 90° C. for 10 to 14 hours to obtain CTAB intercalated illite; the mass ratio of illite to CTAB is 10:0.6 to 1.2; (2) ultrasonically dispersing CTAB intercalated illite and isopropyl titanate triisostearate in ethanol for 10 to 30 minutes, stirring for reaction, filtering, washing, and drying at 60 to 90° C. for 12 to 18 hours to obtain illite modified with titanate coupling agent 131; the mass ratio of the CTAB intercalated illite to isopropyl titanate triisostearate is 1:5 to 9.
2. A water-based ink according to claim 1, characterized in that: The zirconium source is zirconium oxychloride.
3. The water-based ink according to claim 1, characterized in that: The hydrothermal reaction conditions are a hydrothermal reaction at 120-160° C. for 14-20 hours; the drying in the preparation method steps of the EDTA-modified zirconium phosphate is dried at 80-100° C. for 12-18 hours; the stirring reaction in the preparation method steps of the EDTA-modified zirconium phosphate is a stirring reaction at 40-60° C. for 4-8 hours.
4. The water-based ink according to claim 1, characterized in that: In step (1), the stirring reaction is carried out at 50-70° C. for 4-8 hours.
5. The water-based ink according to claim 1, characterized in that: In step (2), the stirring reaction is carried out at 60 to 80° C. for 8 to 12 hours.
6. The water-based ink according to claim 1, characterized in that: The dispersant is octanol polyoxyethylene ether; the defoamer is AFE-3168 organosilicon defoamer; and the film-forming aid is propylene glycol methyl ether.
7. A method for preparing a water-based ink according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: The aqueous polyurethane, EDTA-modified zirconium phosphate, illite modified by titanate coupling agent 131, dispersant, defoamer, film-forming aid and water are stirred at a speed of 3000-4000 rpm for 1-3 hours to obtain the product.
Citation Information
Patent Citations
Water-based ink and printing process thereof
CN116102919A
Two-component solvent-free polyurethane adhesive applied to water-based ink and preparation method of two-component solvent-free polyurethane adhesive
CN117089036A
Environment-friendly printing water-based ink and preparation process thereof
CN118165572A
Preparation method of modified illite for improving performance of natural rubber
CN107189496A
Application of zirconium phosphate nanosheets and scratch-resistant water-based coating
CN108129927A